Mekanisme Penambatan Nitrogen Udara oleh Bakteri Rhizobium Menginspirasi Perkembangan Teknologi Pemupukan Organik yang Ramah Lingkungan - ADNYANA, GEDE MENAKA (Agrotrop : Journal on Agriculture Science; Vol 2 No 2 (2012))
Interaction of microbes with human living in the nature are able to seen from their capabilities improving the environmental by composting waste of agriculture to become organic fertilizer. In the contrary, the epidemic and infectious phatogens are also its contribution. In agriculture sector, the living of microbes has been explored to keep the soil fertile, and to improve growth and plant production. The symbiosis of Rhizobium bacteria with the specific host plant from legumes is able to run because of both side giving a signal, where host plant give an organic molecoles called inducer. From the bacteria side, also give an organic materials called nod factor. The step of nitrogen fixation mechanism can be described from infection of root legume as the first step, followed by the nitrogen fixation by the bacteroid and synthesis of the nitrogen organic by host plant as the last step. These natural processes inspire finding and development of the ecologically organic fertilizer technology.
Keywords: Fixation mechanism, nitrogen, Rhizobium, organic fertilizer, ecologically